Chronic hyperglycemia is an adverse prognostic factor for locoregional recurrence‐free survival in small cell lung cancer patients treated with radical radiotherapy. Issue 18 (4th August 2022) - Kong, Moonkyoo; Lim, Yu Jin
Abstract: Background: Plasma glucose levels might be associated with the severity of tumor hypoxia in patients with cancer. In our previous study, we found that chronic hyperglycemia significantly increased the risk of locoregional recurrence in patients with non‐small cell lung cancer treated with radical radiotherapy (RT). Here, we evaluated the association between plasma glucose levels in terms of hemoglobin A1c (HbA1c) and locoregional recurrence‐free survival in patients with limited‐stage small cell lung cancer treated with radical RT. Methods: We retrospectively analyzed the clinical data of 59 patients with small cell lung cancer. HbA1c levels were measured 1 week before the start of RT. Survival outcomes were analyzed according to HbA1c levels. Multivariable analysis was conducted to identify whether HbA1c level was a significant prognostic factor for survival. Results: The 1‐, 2‐, and 3‐year locoregional recurrence‐free survival rates were 90.9, 86.1, and 78.9%, respectively, in the low HbA1c group, and 45.1, 27.1, and 20.3%, respectively, in the high HbA1c group ( p  < 0.001). The 1‐, 2‐, and 3‐year distant metastasis‐free survival rates were 67.2, 57, and 57%, respectively, in the low HbA1c group, while it was 56.6, 24.9, and 24.9%, respectively, in the high HbA1c group ( p  = 0.024). HbA1c level remained a significant prognostic factor for locoregional recurrence‐free survival in the multivariable analysis ( p  = 0.010). Conclusions: Chronic hyperglycemia is a significant prognostic factor for locoregional recurrence‐free survival in patients with limited‐stage small cell lung cancer treated with radical RT. Routine monitoring of plasma glucose levels and aggressive glycemic control should be conducted to prevent locoregional recurrence. Abstract : Chronic hyperglycemia can aggravate tumor hypoxia and hypoxic tumors are resistant to RT. Therefore, chronic hyperglycemia can decreases the RT response.